Pengaruh Expressive Writing Therapy Terhadap Kecenderungan Depresi pada Staf Akademik Fakultas Kedokteran Universitas Malikussaleh - Nora Maulina; Anna Millizia; Moulida Aziza (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Depression is a common mental disorder with the highest prevalence. Based on the causative factors, depression is divided into several factors, namely biological factors, genetic factors, and psychosocial factors. Psychosocial factors a number of clinicians believe that life events play a major role in depression. According to the International Labor Organization (ILO), it shows that stress in the workplace or work environment can cause depression in workers. This study aims to determine the difference in scores using the BDI-II questionnaire before and after the expressive writing therapy intervention on the academic staff of the Faculty of Medicine, Malikussaleh University. The method used in this study was a quasi-experimental (quasi-experimental) research design in the form of a one group pretest-posttest design and using primary data taken through expressive writing therapy intervention to 31 respondents. The results showed that 27 respondents (87.09%) experienced a decrease in the BDI-II score, 4 (12.90%) respondents had a fixed score and none (0%) experienced an increase in scores before and after the intervention. Statistical analysis using the Wilcoxon alternative test with the results obtained a significant value of 0.000 (P <0.05), then statistically there is a statistical difference in the BDI-II depression trend mean scores before and after expressive writing therapy intervention on academic staff of the Faculty of Medicine, Malikussaleh University. The conclusion of this study is that there is an effect of expressive writing therapy on the tendency of depression in the Academic staff of the Faculty of Medicine, Malikussaleh University.